2003
DOI: 10.1038/sj.bmt.1704111
|View full text |Cite|
|
Sign up to set email alerts
|

Immunomodulatory effects of human foetal liver-derived mesenchymal stem cells

Abstract: Summary:Adult mesenchymal stem cells (MSCs) have been suggested to decrease lymphocyte proliferation in vitro. We hypothesised that foetal MSCs (fMSCs) would have an immunosuppressive effect on allograft responses in vitro. Human MSCs were isolated and cultured from firsttrimester foetal livers and characterised by flow cytometry. fMSC stained positive for CD29, CD44, CD166, CD105, SH-3 and SH-4, and negative for CD14, CD34 and CD45. When plated on adipogenic, chondrogenic and osteogenic media, fMSC differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(136 citation statements)
references
References 30 publications
(38 reference statements)
5
129
0
2
Order By: Relevance
“…The immunomodulatory property of MSCs were discovered more than a decade ago (Bartholomew et al, 2002;Gotherstrom et al, 2003;Le Blanc et al, 2003). Immunomodulation of MSCs can occur via different mechanisms; the most common mechanism occurs via cytokine signals (released by MSCs); the cytokines include IFN-gamma, TNF-alpha, IL-1 beta, and IL-2 (De Miguel et al, 2012;English, 2013;Yagi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The immunomodulatory property of MSCs were discovered more than a decade ago (Bartholomew et al, 2002;Gotherstrom et al, 2003;Le Blanc et al, 2003). Immunomodulation of MSCs can occur via different mechanisms; the most common mechanism occurs via cytokine signals (released by MSCs); the cytokines include IFN-gamma, TNF-alpha, IL-1 beta, and IL-2 (De Miguel et al, 2012;English, 2013;Yagi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Human MSC were isolated from bone marrow (BM) aspirates from the iliac crest of healthy donors, ranging in age from 9 to 47 y. MSC were isolated and cultured, according to previously reported methods [15][16][17] Mononuclear cells from adult BM were isolated from Percoll-separated BM and resuspended in hMSC medium consisting of Dulbecco's modified Eagle's medium-low glucose (DMEM-LG) (Life Technologies, Gaithersburg, MD, USA), supplemented with 10% fetal bovine serum (FBS) (Sigma) and 1% antibioticantimycotic solution (Life Technologies) and plated at 3 Â 10 7 cells/175 cm 2 in Falcon flasks (Becton Dickinson, San Jose, CA, USA). The serum lot used was selected on the basis of optimal MSC growth with maximal retention of Assessment of differentiation Differentiation of preadipocytes and hMSC was assessed by determining glycerol-3-phosphate-dehydrogenase (GPDH) activity and staining with the triglyceride-specific dye Oil Red O as described before.…”
Section: Human Msc Culturesmentioning
confidence: 99%
“…Thus, the normal sequential developmental migrations of stem cells in the fetus might increase the homing and engraftment capability of fl-MSCs after cell transfer into fetal tissues (eg, hematopoiesis starts at the yolk sac or aorto-gonado-mesonephric region, migrates to the fetal liver, and finally resides in the bone marrow [32]). We [23] and others [22] have previously reported that fl-MSC possess at least some of the immunomodulatory properties found in adult-derived MSCs. In addition MSCs and, particularly, fetal MSCs are efficiently transduced with integrating vectors and express the corresponding transgene without losing stemness and differentiation capabilities [12,23,33].…”
Section: Moreno Et Almentioning
confidence: 99%
“…Using fetal instead of adult donor cells for in utero transplantation approaches may also offer some benefit. Indeed, fetal MSCs from different tissue sources are present in higher amounts than their adult MSC counterparts, and show superior proliferative capacity once isolated [22,23].…”
Section: Introductionmentioning
confidence: 99%